'Seated at the Right Hand of the Father': The Meaning of the Empty Tomb Narrative in Mark. Issue 2 (1st April 2023) - Bond, Helen K.
Abstract : The following essay argues that Mark's empty tomb narrative taps into broader Jewish and Graeco-Roman cultural assumptions in which the disappearance of a body might suggest that the person concerned had been taken up into the realm of the gods. The purpose of Mark 16.1–8, therefore, is not to prove Jesus's physical, fleshly resurrection, but rather to show that he is now in the heavenly realm, 'seated at the right hand of the Father' (14.62).